THE INFLUENCE OF GREENWASHING PERCEPTION AND WORD-OF-MOUTH TOWARD GREEN PURCHASE INTENTION ON SINGLE-USE PLASTIC PRODUCTS - Nurul Marliza Putri Hesti; Hafiz Rahman; Donard Games (Halu Oleo University, 2024)
The background of this research is the misleading eco-friendly claim made by manufacturers of products with disposable packaging (Single-Use Plastic Products). These practices are referred to as greenwashing. The purpose of this study is to examine the impact of greenwashing perceptions and word-of-mouth on green purchase intention towards environmentally friendly products on products that use Single-Use plastic packaging, especially bottled mineral water products (Air Minum dalam Kemasan/AMDK). The research method uses a quantitative approach. The sampling technique uses purposive sampling, where respondents are selected by considering certain criteria. The number of samples in this study was 160 respondents who live in Padang City, Indonesia. The data collection technique uses a survey method with questionnaires both online and offline. The data processing method uses Structural Equation Modeling - Partial Least Square (SEM-PLS) v4. The results showed that greenwashing perception has a negative effect on green purchase intention. This means that the higher the greenwashing perception of consumers, the lower their intention to purchase disposable packaging products. Meanwhile, word-of-mouth has a positive and significant effect on green purchase intention.